UÅÃ»l al-Fiqh versus Hermeneutika tentang Pengembangan Pemikiran Hukum Islam Kontemporer - Fanani, Ahwan (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
The philosophy of Islamic Law (uÅÃ»l al-fiqh) has been known as occupying the central positionin the whole structure of Islamic jurisprudence. Its method and logic of legal extrapolation has dominated not only the legal sphere of the jurists but also influenced the philosophers and the scholastics in their method and way of thinking. UÅÃ»l al-fiqh is mainly deductive in its approach and is concerned with the analysis of linguistics. Now with the developments of new methods in legal and linguistic studies, many scholars have attempted to introduce new way of interpreting Islamic law by bringing up hermeneutics as the main tool. Hermeneutics is about interpreting text by taking into consideration the cultural and personal backgrounds of the author. It also teaches that in reading a text, a reader must be neutral in that he should not have in mind an a priori knowledge and assumption about the subject. This paper is concerned with exploring the dynamics of both uÅÃ»l al-fiqh and hermeneutics in the context of developing the Islamic Law in contemporary life.